Hard and soft logical information. (6th April 2017) - Allo, Patrick
Abstract: In this article I use the distinction between hard and soft information from the dynamic epistemic logic tradition to extend prior work on informational conceptions of logic to include non-monotonic consequence-relations. In particular, I defend the claim that at least some non-monotonic logics can be understood on the basis of soft or 'belief-like' logical information, and thereby question the orthodox view that all logical information is hard, 'knowledge-like', information.